2017
DOI: 10.1186/s12985-017-0900-8
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel Newcastle disease virus (NDV) neutralization test based on recombinant NDV expressing enhanced green fluorescent protein

Abstract: BackgroundNewcastle disease is one of the most important infectious diseases of poultry, caused by Newcastle disease virus (NDV). This virus is distributed worldwide and it can cause severe economic losses in the poultry industry due to recurring outbreaks in vaccinated and unvaccinated flocks. Protection against NDV in chickens has been associated with development of humoral response. Although hemagglutination inhibition (HI) assay and ELISA do not corroborate the presence of neutralizing antibodies (nAbs); t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
0
28
0
Order By: Relevance
“…However, it is highly laborious and very slow, yielding results only after nearly one week. Interestingly, Chumbe et al [ 75 ] reported the development of an improved VNT using a recombinant NDV engineered to constitutively express GFP. The newly developed assay has been shown to give conclusive results within 24 hours without the need for any additional staining procedure.…”
Section: Diagnosismentioning
confidence: 99%
“…However, it is highly laborious and very slow, yielding results only after nearly one week. Interestingly, Chumbe et al [ 75 ] reported the development of an improved VNT using a recombinant NDV engineered to constitutively express GFP. The newly developed assay has been shown to give conclusive results within 24 hours without the need for any additional staining procedure.…”
Section: Diagnosismentioning
confidence: 99%
“…The clinical symptoms of ND are similar to those of some other diseases including low pathogenic avian influenza, infectious laryngotracheitis, and infectious bronchitis, all showing the respiratory sign of dyspnea, so they may be confused with each other in the clinical diagnosis ( Chumbe et al., 2017 , Giovanni et al., 2017 ). A specific, sensitive, and convenient diagnostic method can provide strong support for the prevention and treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The serum samples from different vaccinated groups, taken at day 3 wpi, were subjected to HI assay using 1% chicken red blood cells in accordance with the standard method ( Alexander, 2000 ). The antibody titer was measured by VN assay with modifications ( Chumbe et al., 2017 ). Briefly, monolayer cultures of CEF cells were seeded at 80–90% confluence in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%